Participação popular e emancipação social: um estudo sobre o Planejamento Participativo de Sergipe (PP) - Carregosa, Antonio Santana (2009)
The aim of this paper is to discuss the relationship between popular participation and social emancipation in the Sergipe Participatory Planning (PP). It seeks to combine theoretical with practical field research to obtain operational categories to contextualize the experience and monitor its first steps. Thus, it was observed that the idea of popular participation in Brazil dates from the period of democratization, which strengthened the debate about the relationship between democracy and citizenship decisively influencing the development of the Constitution of 1988. This debate referenced a lot about classic experiments in participatory democracy as the Paris Commune and the Workers' Councils, which retrieves the principles of social control and the "redistribution". With the promulgation of the new Constitution and the rise of populist governments, participatory democracy in the form of Participatory Budgeting (PB) has spread across the country with the managements of PT (Partido dos trabalhadores, Workers Party) in Porto Alegre, the capital of Rio Grande do Sul, Brazil, where was the experience more successful. Becoming brand of PT administrations, the PB is also implemented in Aracaju, the capital of Sergipe, with the victory of the PT in 2000. In 2007 the PT took over the government of Sergipe and begins construction of the PP with the goal to correct the social inequities in the state. Under the coordination of SEPLAN and with the participation of various institutions, the new government establishing the eight Territories Planning Central Hinterland, High Hinterland, Low San Francisco, South Central, Greater Aracaju, Sergipe East, Middle and South Hinterland of Sergipe - and began the process of consulting the population. Have been held two rounds of Municipal Conferences, four Territorial Conferences and three State Conferences of the PP, involving more than 28,000 people. The actors are hegemonically between the popular sectors and the presented demands, and they refer mainly to the most basic questions of citizenship. Also if note that PP has stimulated new relations and new practices of these actors, besides fostering a mutual learning between experts and society at large. About social control, it is observed that the PP has not built the necessary tools yet. Moreover, it is understood that the PP is at a turning point in which the definition of an institutional architecture and the presentation of concrete results can ensure its consolidation as a means of propelling of a new political culture - democratic and emancipatory in Sergipe.